Contribution of Singing Subject to the Effectiveness of Foreign Language Trainning Program at Vietnam National University Hanoi - Van Phuc, Nguyen (VNU Journal of Science: Education Research; Vol 38 No 2DO - 10.25073/2588-1159/vnuer.4655, 2022)
Bachelor standard programs (English Language major) include comprehensive subjects which help students to develop the skills and knowledge needed to become professionals at their field. In the general aim of the program, there are several contents that can be enhanced in the level of education effectiveness by the support of singing lessons. This paper analyzes and provides several suggestions on how to suitably apply singing lessons in order to contribute to the enhancement of educational effectiveness of this program’s structure at Vietnam National University Hanoi.